2022
DOI: 10.1109/tits.2021.3092276
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Big Data and Coordinated Charging for Effective Taxi Fleet Electrification: The 100% EV Conversion of Shenzhen, China

Abstract: vehicles (EVs), but long charging durations and limited charger availability have prevented rapid adoption. Leveraging over two weeks of high-resolution GPS and battery data from almost 20,000 EVs in the all-electric Shenzhen taxi fleet, we analyze the potential to improve fleet-wide operations by optimizing both the location and timing of vehicle charging. We construct machine learning models to predict travel time, queuing time at charging stations, and charge consumption by time of day. Contrary to the emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Bauer et al (2020) , showed that this inefficiency is largely due to a lack of data: without proper information on the best places and times to charge, drivers tend to charge at large stations right before they end their shifts, during afternoon peak demand. The authors found that providing drivers with complete information including forecasts of trip demand could reduce revenue losses by up to 90%, and even just providing accurate information on queues at each charging station could reduce overall queuing time by half.…”
Section: Coordinated Charging Enables Effective Electrificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Bauer et al (2020) , showed that this inefficiency is largely due to a lack of data: without proper information on the best places and times to charge, drivers tend to charge at large stations right before they end their shifts, during afternoon peak demand. The authors found that providing drivers with complete information including forecasts of trip demand could reduce revenue losses by up to 90%, and even just providing accurate information on queues at each charging station could reduce overall queuing time by half.…”
Section: Coordinated Charging Enables Effective Electrificationmentioning
confidence: 99%
“…We assume that vehicles must be replaced at 80% of original capacity when uncoordinated, and at 50% when coordinated, as found in Bauer et al (2018) . Revenue lost due to charging is based on Bauer et al (2020), and includes the opportunity cost from time spent both queuing and charging. , In both (c) and (d), we assume an annual discount rate of 5%. See Supporting Information for more details on calculations and assumptions.…”
mentioning
confidence: 99%
See 1 more Smart Citation